Psychosemantic Space of Preconventional, Conventional and Post-Conventional Moral Consciousness of Personality - Tymosh, Yuliya (Psychological Prospects Journal, 2018)
The article presents the results of the theoretical and empirical research of various stages and levels of moral consciousness of the student’s personality, as well as the psychosemantic space of these stages is distinguished. The main purpose of psychosemantic research is the reconstruction of semantic spaces – the presentation of the content of consciousness, the representation of its semantic structure in the whole variety of possible relationships. It is established that all the manifested stages of moral consciousness: preconventional, konventional, post-conventional are manifested mainly on a high level. Accordingly, students flexibly use different types of moral consciousness depending on the situation. It has been shown that, demonstrating preconventional, conventional and post-conventional stages, students are mostly at a high level of their formation. We observe the same associations with high frequency in people with different stages of moral consciousness, among them: conscience, courtesy, honesty. The common semantic universals of morality for these individuals prove in favor of the simultaneous expression of different stages of moral consciousness in youth and the possibility of manifestation of these stages in accordance with the situation. At the same time, there are differences that express the specifics of each of the stages. Thus, at the preconventional stage we see associations: assistance, person, friend, partner, and that testifies to the importance of mutually beneficial relations between people. In persons with a conventional stage, we observe associations: law, rule, justice, whereas at the post-convention stage: goodness, dignity, honor, which did not occur in previous stages. A meaningful analysis of associations confirms the qualitative interpretation of each stage and expresses the peculiarities of students’ moral consciousness. We consider promising the further research of moral consciousness in the context of the integral identity of students.